Independent accounts the possibilities for auditor independence in the age of financial scandal - Lehman, Cheryl R. (Advances in public interest accounting ;, 2006)
Returning to its roots in activism and economic justice, this issue exposes accounting practice as a contested terrain by examining its role as a social force encompassing issues of value, governance, ethics, politics, and class. Arguing that the view of the discipline as objective and fair is a myth, these papers illuminate the detrimental social consequences of failing to recognize accountings role in the social environment. Investigating accounting's use of independence as a protective shield in obscuring winners and losers regarding financial activity, the papers illustrate accountings contribution to the failures of free markets worldwide: systemic global poverty, questionable privatization of public enterprises and public goods, and greater divides between so-called first and third world nations. Revealing the integrated nature of regulation, accounting, and ethics, the papers in this volume question the logic of merely fine tuning current systems proposing instead visionary and innovative change by probing deeply into our beliefs, social practices, and consciousness.